Is Liberal Socialism Possible? Reflections on "Real Utopias"*. (December 2020) - Katznelson, Ira
This essay, written in memory of Erik Olin Wright (1947–2019), explores the possibility of liberal socialism. Wright sought to rescue both liberalism and socialism from their demonstrated capacity for depredation. His legacy challenges reformers to proceed with the audacity of real, and realistic, utopianism together with an awareness that, unfortunately, the obverse of an appealing utopianism always beckons.